Β-Hydroxy-β-methylbutyrate modulates lipid metabolism in adipose tissues of growing pigs. Issue 9 (23rd August 2018) - Duan, Yehui; Zhang, Lingyu; Li, Fengna; Guo, Qiuping; Long, Cimin; Yin, Yulong; Kong, Xiangfeng; Peng, Mijun; Wang, Wence
Abstract : Background : The effects and roles of the leucine (Leu) metabolite β-hydroxy-β-methylbutyrate (HMB) in lipid metabolism in adipose tissues of pigs are still unknown. Abstract : Background : The effects and roles of the leucine (Leu) metabolite β-hydroxy-β-methylbutyrate (HMB) in lipid metabolism in adipose tissues of pigs are still unknown. Objectives : This study was conducted to investigate the effects of excess Leu versus HMB on growth, carcass traits, and lipid metabolism in adipose tissues of growing pigs. Methods and results : Compared to control, the Leu/HMB group significantly increased/reduced weight of total fat mass, respectively, with a concurrent increase of serum adiponectin concentration ( P < 0.05). Moreover, dietary HMB supplementation regulated the expression of genes involved in adipose tissue function, accompanied by increases/decreases in the phosphorylation of AMPKα/mTOR in perirenal adipose tissue, respectively ( P < 0.05). Serum IL-15 concentration and the mRNA abundance of IL-15, PGC-1α, and NRF-1 were also increased in the HMB group ( P < 0.05). Conclusions : HMB supplementation can regulate adipose tissue function including fatty acid oxidation, lipolysis, and adipokine secretion. These effects may be partly mediated by AMPKα-mTOR pathway and associated with mitochondrial biogenesis, the AMPK-PGC-1α axis, and myokines secreted by muscle tissues.